Understanding Streaming Instabilities in the Limit of High Cosmic-Ray Current Density - Emily Lichko; Damiano Caprioli; Benedikt Schroer; Siddhartha Gupta (The Astrophysical Journal)
A critical component of particle acceleration in astrophysical shocks is the nonresonant (Bell) instability, where the streaming of cosmic rays (CRs) leads to the amplification of magnetic fields necessary to scatter particles. In this work we use kinetic particle-in-cell simulations to investigate the high-CR-current regime, where the typical assumptions underlying the Bell instability break down. Despite being more strongly driven, significantly less magnetic field amplification is observed than in low-current cases, an effect due to the anisotropic heating that occurs in this regime. We also find that electron-scale modes, despite being the fastest growing, mostly lead to moderate electron heating and do not affect the late evolution or saturation of the instability.